Objectivity According to the Public: Contribution to the Media Literacy - Podzimek, Jan (Civilia, 2020)
This study analyses the idea of the media objectivity according to the Czech public. It describes various forms of unobjectivity, and the idea of how the objectivity should be fulfilled. An important part of this study is the idea of how the media and journalists operate in connection with the objectivity, of the content of the relevant laws and of the role of the media in the society - all according to the public. The conclusion relates the topic to the media literacy, because the knowledge of the most frequent misunderstandings and shortcomings in the image of objectivity according to the public offers a space for its elimination. The study uses a unique research sample made up by anonymised complaints on infringement of the objectivity sent to the Czech Council for Radio and Television Broadcasting.
Keywords: Objectivity; Media Literacy; Audiences